A multidentate polymer microreactor route for green mass fabrication of mesoporous NaYF4 clusters. Issue 11 (17th January 2022) - Li, Yameng; Zhang, Xiaozeng; Chao, Zhicong; Gan, Minglong; Liao, Jinsheng; Ye, Xinyu; You, Weixiong; Fu, Junxiang; Wen, Herui
Abstract : We report a "multidentate polymer microreactor" method for the creation of secondary structures of colloidal nanocrystals. Abstract : We report a "multidentate polymer microreactor" method for the creation of secondary structures of colloidal nanocrystals. Using NaYF4 :Yb, Er as an example, we demonstrate that the use of sodium polyacrylate (PAAS) as a "multidentate polymer microreactor" allows the controllable growth of primary nanocrystals and induces aggregation of the nanocrystals into well-defined mesoporous clusters.